Use of skin-fascial flaps on perforating vessels in the surgical treatment of skin melanoma - Yu. V. Przhedetskiy; V. V. Pozdnyakova; N. A. Maximova; O. V. Khokhlova; N. A. Zakharova; M. G. Ilchenko; V. Yu. Przhedetskaya (Южно-Российский онкологический журнал)
Purpose of the study. Improving the results of surgical treatment of melanoma of the skin of the extremities by using skin-fascial flaps on perforating vessels.Patients and methods. In 42 patients with limb skin melanoma T1–3N0M0, the closure of a skin defect was performed by islet flaps on perforating vessels. Perforating vessels of the donor zone were detected with an assessment of the blood supply of the flaps in the pre- and postoperative period using ultrasound and marking of perforants with adjustment of the preliminary marking of the flaps.Results. Permanent perforating vessels with a diameter of more than 1 mm were used. After excision of the tumor, on the opposite sides of the wound defect, taking into account the location of the perforating vessels, flaps were taken, with further mobilization by excision of the fiber and muscle fascia, they were separated from the underlying tissues while maintaining the integrity of the supply vessels. The circulatory state of the selected flaps was determined by skin color and capillary response to digital pressure. The flaps were displaced to the center, covered the area of the defect and sutured with single sutures, the edges of the donor wound were mobilized, sutured with single sutures until light tension appeared and sutured into the remaining wound defect. In the postoperative period, the determination of the parameters of the blood flow of perforating vessels showed the absence of hemodynamically significant violations of the blood flow during the movement of the flap. Transient ischemia of one of the oncoming flaps after surgery developed in 11.9%, marginal necrosis of the distal flap — in 7.1% of cases. A normotrophic scar was formed, with a width of not more than 0.3 cm, which aesthetically satisfied 92.8% of patients. Assessment of two-year relapse-free survival showed a complete absence of local relapses.Conclusion. The flaps vascularized by perforating vessels have high viability, are identical in color and texture to the skin of the recipient area, and the close proximity to the receiving area contributes to minimal deformation of the donor area, which increases the radicality of the operation, reduces the incidence of postoperative complications and improves аesthetic and functional results.